Quality of care provided to hospitalized under-five children suffering from severe malaria at Kamuzu Central Hospital, Lilongwe, Malawi - Nyirongo Chiluzi, Blessings Chimwemwe (2021)
Background: Severe malaria, the number one cause of morbidity and mortality in Africa and Asia causes imminent death in an under-five child if left unattended to. As such provision of timely, quality care to this age-group helps save lives and it also results in 46% reduction of all neurological impairments. To explore and describe the quality of care that is provided to hospitalized underfive children suffering from severe malaria at Kamuzu Central Hospital, Children’s’ Special Care ward. This was a descriptive, study that utilized qualitative approach. Purposive sampling was used to recruit participants. A semi-structured interview guide was used to collect data. Data was collected through face to face in-depth interviews by the researcher from 24th June 2014 to 25th July 2014. A digital tape recorder was used to record interviews with permission of the participants. A total of 25 Health Care Workers (HCWs’) were interviewed. Thematic Content Analysis (TCA) was used to analyze data manually. Demographic data was collected using a questionnaire computed and analyzed using descriptive statistics. Despite the fact that triage was implemented and that very sick children were priotized for urgent care, findings generally indicated that the quality of care that majority of hospitalized under-five children suffering from severe malaria received was poor and below standard. Major attributable reasons for poor quality care were severe shortage of Health Care Workers, poor and unfriendly infrastructures and shortage of essential medical supplies required for resuscitation. Severe shortage of staff, poor infrastructures and shortage of essential medical supplies required for resuscitation resulted in delivery of poor quality care by Page health care workers. It is therefore, recommended that more Health Care Workers should be deployed, there is need for infrastructure renovations and increased hospital funding by government to improve resource mobilization and availability.